HUBUNGAN STATUS GIZI IBU HAMIL ATERM DENGAN BERAT BADAN LAHIR BAYI - Baiq Ricca Afrida (Jurnal Akademika Baiturrahim Jambi, 2019)
The nutritional status of the mother before and during pregnancy is one of the important factors that influence the growth and development of the intrauterine fetus. Chronic lack of energy will cause the birth of babies with low birth weight. Risk factors for low birth weight events are influenced by maternal conditions accompanied by malnutrition and other maternal factors. This study aims to determine the relationship between the nutritional status of pregnant women at term with the baby's birth weight. This study was an observational study with a cross sectional design. The sample in this study was mothers in maternity clinic who fulfilled the inclusion criteria. The sampling technique was consecutive sampling. The number of samples in this study were 50 people. Data analysis was performed by correlation statistical test. The results showed a significant relationship between maternal nutritional status (size of the upper arm circumference (p = 0,000) and birth weight of the baby. The conclusion were maternal nutritional status is very influential on birth weight of babies born